QARAQALPAQ TILINDEGI BOLÍMLÍ – BOLÍMSÍZLÍQTÍŃ LINGVISTIKALÍQ TÁBIYATÍ - Orazımbetov, A.Q.; Uzaqbaeva, N. (SCIENCE and SOCIETY, 2021)
This article is devoted to the linguistic nature of affirmative and negative meanings in the Karakalpak language and its multidimensionality in relation to all language systems.